Evaluación agronómica y morfológica de tres variedades de col (Brassica oleracea) a dos sistemas de fertilización en el sector Negroyaco cantón, Guaranda provincia Bolívar - Escobar Barragán, Luis Gustavo (2020)
In our country, the provinces of Tungurahua, Chimborazo, Pichincha, Azuay and Cotopaxi are the main producers of Col, in the Bolívar province its production is transiently mainly in family gardens. This investigation was carried out in the sector of Negroyaco, Cantón Guaranda province Bolívar. The objectives set were: i) Agronomically and morphologically characterize the three varieties of cabbage. ii) Evaluate the response of the three varieties of cabbage to chemical and organic fertilization. iii) Establish an Economic Analysis of Partial Budget (AEPP) and Marginal Rate of Return (TMR). A randomized complete block design (DBCA) was analyzed in a 3x3 factorial arrangement with 3 repetitions obtaining 9 treatments. Factor A corresponds to the varieties (Milan, Fresco, Tokita) and factor B the types of fertilization. A combined variance analysis will be considered to determine the 5% Tukey tests to compare promises of factor A and interaction of factors A x B when the Fisher is significant, correlation analysis and linear regression, economic analysis of partial budget and calculation of the Marginal Rate of Return. The most important variables that contribute to increase the yield were: Leaf width, Plant height, Cabbage diameter and Leaf length. There was a highly significant effect on yield, this is due to the different genetic characteristics of the varieties, and the soil and climate conditions of the sector. The best yield was from T5: A2B2 (Fresh Variety with organic fertilization) with an average of 19206 Kg / Ha. Finally this research gave us a new alternative for agricultural production in the area, thus improving the productive matrix in the Bolívar province.